2022
DOI: 10.3389/pore.2022.1610450
|View full text |Cite
|
Sign up to set email alerts
|

GPNMB-Positive Cells in Head and Neck Squamous Cell Carcinoma—Their Roles in Cancer Stemness, Therapy Resistance, and Metastasis

Abstract: Objective: Despite the use of surgical and chemoradiation therapies, head and neck squamous cell carcinoma (HNSCC) still has a poor prognosis. Immune checkpoint inhibitors have been shown to prolong life expectancy but have limited efficacy. Glycoprotein nonmetastatic melanoma protein B (GPNMB) has received significant attention in breast cancer treatment, in which it has been associated with cancer stem cells (CSCs) and epithelial-mesenchymal transition (EMT); however, the function of GPNMB in HNSCC is comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This could be astrocytes or a subgroup of glioma cells. For breast and Head and Neck Squamous Cell carcinoma it has been reported that a subgroup of cancer stem cells express GPNMB and utilize it to persist [ 22 , 46 , 47 ]. Whether GPNMB + IBA1 − cells are these cancer stem cells remains an open issue.…”
Section: Discussionmentioning
confidence: 99%
“…This could be astrocytes or a subgroup of glioma cells. For breast and Head and Neck Squamous Cell carcinoma it has been reported that a subgroup of cancer stem cells express GPNMB and utilize it to persist [ 22 , 46 , 47 ]. Whether GPNMB + IBA1 − cells are these cancer stem cells remains an open issue.…”
Section: Discussionmentioning
confidence: 99%
“…GPNMB has been implicated in the promotion of cancer cell metastasis through multiple mechanisms. Prior research has identified GPNMB as a crucial molecular mediator that facilitates the acquisition of aggressive traits by inducing matrix metalloproteinases (MMPs) and epithelialmesenchymal transition (EMT) [31][32][33]. Additionally, GPNMB, known for its role as a negative regulator of T cell activation, exhibits potent immunosuppressive properties in the context of cancer [11].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, immune infiltration, EGFR signalling, STAT3 and hypoxia have all been linked to basal subtypes [22][23][24][25][26][27] , suggesting that GPNMB may play a role in stimulating angiogenesis in basal tumours. GPNMB is a glycoprotein that has been shown to promote the aggressiveness of multiple cancer types, including bladder cancer [28][29][30] . While we found no significant prognostic evidence when analysing GPNMB RNA levels in bulk sequencing, high GPNMB levels measured by immunohistochemistry in bladder cancer was previously correlated with a worse prognosis 29 .…”
Section: Discussionmentioning
confidence: 99%